2017
DOI: 10.3389/fendo.2017.00325
|View full text |Cite|
|
Sign up to set email alerts
|

Effects on Subclinical Heart Failure in Type 2 Diabetic Subjects on Liraglutide Treatment vs. Glimepiride Both in Combination with Metformin: A Randomized Open Parallel-Group Study

Abstract: ObjectiveWe aimed to investigate the effect of liraglutide treatment on heart function in type 2 diabetes (T2D) patients with subclinical heart failure.MethodsRandomized open parallel-group trial. 62 T2D patients (45 male) with subclinical heart failure were randomized to either once daily liraglutide 1.8 mg, or glimepiride 4 mg, both add on to metformin 1 g twice a day. Mitral annular systolic (s′) and early diastolic (e′) velocities were measured at rest and during bicycle ergometer exercise, using tissue Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
(62 reference statements)
1
27
0
1
Order By: Relevance
“…Some studies have investigated the effect of liraglutide on LV diastolic function. Nystrom et al [26] found no change in echocardiography-derived indices of myocardial relaxation, E/Ea or LV ejection fraction in their non-blinded randomized study with 62 DM2 patients with subclinical heart failure receiving either liraglutide or glimepiride treatment. A double-blind randomized trial in 33 patients with DM2 who underwent a 16 week exercise program with addition of either liraglutide or placebo, showed significantly lower E/Ea in liraglutide treated patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the effect of liraglutide on LV diastolic function. Nystrom et al [26] found no change in echocardiography-derived indices of myocardial relaxation, E/Ea or LV ejection fraction in their non-blinded randomized study with 62 DM2 patients with subclinical heart failure receiving either liraglutide or glimepiride treatment. A double-blind randomized trial in 33 patients with DM2 who underwent a 16 week exercise program with addition of either liraglutide or placebo, showed significantly lower E/Ea in liraglutide treated patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no severe hypoglycaemic event during the study (no groups) although a numerical (non-significant) higher numbers of mild hypoglycaemia in the glimepiride group was observed. 6 Despite this HR was not increased in patients treated with glimepiride compared to patients treated with liraglutide, making this consideration less important. Because of dropouts and technical hitches, full data were available for 85% of the study population (53 out of 62) and subsequently analysed per-protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The main results of this study have been published elsewhere. 6 Briefly, T2D patients who had glycated haemoglobin A1c (HbA1c) of 6.3% -11% (45-97 mmol/mol) were eligible if they had not been previously treated with GLP-1 RA, dipeptidyl peptidase-4 inhibitors or glimepiride. Patients who met these criteria were invited for echocardiographic screening, in which one of the following criteria had to be fulfilled: left ventricle ejection fraction ≤50% or evidence of diastolic dysfunction.…”
Section: Trial De S I G Nmentioning
confidence: 99%
“…A randomized, placebo-controlled study of 33 patients with T2DM patients showed that liraglutide blunted the effect of supervised training on diastolic function (eʹ), which in the placebo groups improved [ 18 ]. In a randomized open-label study, patients with T2DM and subclinical heart failure did not improve diastolic function parameters after 18 weeks of liraglutide therapy when compared to glimepiride treatment [ 19 ]. In a small study of 23 patients LV filling pressure was improved after liraglutide therapy, but no effect on myocardial relaxation (eʹ) was seen [ 20 ].…”
Section: Discussionmentioning
confidence: 99%